2021
DOI: 10.1021/acs.molpharmaceut.0c00977
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin-Loaded PLGA-DMSA Nanoparticles: A Novel Strategy to Treat Melanoma Lung Metastasis

Abstract: The flavone apigenin (APG), alone as well as in combination with other chemotherapeutic agents, is known to exhibit potential anticancer effects in various tumors and inhibit growth and metastasis of melanoma. However, the potential of apigenin nanoparticles (APG-NPs) to prevent lung colonization of malignant melanoma has not been well investigated. APG-loaded PLGA-NPs were surface-functionalized with meso-2,3-dimercaptosuccinic acid (DMSA) for the treatment of melanoma lung metastasis. DMSAconjugated APG-load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The cell line viability study reported by different researchers, reported marked activity of AN in different cell lines. Sen et al, formulated AN-PLGA nanoparticles and exhibited 7.8 and 10.8 times less IC 50 than the pure drug against a lung cancer cell line (B16F10 and A549) [ 53 ]. In another study, Zhai et al, formulated and exhibited approximately 5-fold lesser IC 50 value against HepG2 and MCF-7 cell lines than pure AN solution [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cell line viability study reported by different researchers, reported marked activity of AN in different cell lines. Sen et al, formulated AN-PLGA nanoparticles and exhibited 7.8 and 10.8 times less IC 50 than the pure drug against a lung cancer cell line (B16F10 and A549) [ 53 ]. In another study, Zhai et al, formulated and exhibited approximately 5-fold lesser IC 50 value against HepG2 and MCF-7 cell lines than pure AN solution [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, new formulations or methods should be developed to improve solubility of AP and its bioavailability [86] . Numerous kinds of nanomaterials such as metallic–based nanomaterials, lipid-based and polymeric nanoparticles were developed in order to the highly effective delivery of AP [86] , [87] , [88] . The oral bioavailability of AP nanoparticles was about 5 fold upper compared to the naked AP, and this formulation shows no toxic outcome on the organs of mice [89] .…”
Section: Enhanced Bioavailability Of Ap Via Nanoparticlesmentioning
confidence: 99%
“…The results showed DMSA-conjugated flavone AP causes the COX-2 expression to be down regulated COX-2 expression in B16F10 cells. In fact, decrease in the COX-2 level can be an inhibitor of melanoma cell invasion [88] . Encapsulated AP with nanomaterials such as PLGA showed enhanced effectiveness in treatment of cancer.…”
Section: Enhanced Bioavailability Of Ap Via Nanoparticlesmentioning
confidence: 99%
“…Apigenin (Figure 2d) is mainly found in fruits and vegetables and can be isolated from the buds and flowers of Hypericum perforatum [52,64]. Apigenin can induce the apoptotic process in melanoma cells by activation of mitochondrial apoptotic pathway caused by alterations in mitochondrial membrane and increased activity of caspases [12,65]. Furthermore, one study found apigenin caused DNA fragmentation indicating an early apoptotic stage [65].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Apigenin can induce the apoptotic process in melanoma cells by activation of mitochondrial apoptotic pathway caused by alterations in mitochondrial membrane and increased activity of caspases [12,65]. Furthermore, one study found apigenin caused DNA fragmentation indicating an early apoptotic stage [65]. In another study, it was shown that apigenin decreased the invasion of cells in vitro and inhibited melanoma growth and metastatic potential in vivo [54].…”
Section: Flavonoidsmentioning
confidence: 99%